Selective ophthalmic artery chemosurgery (SOAC) for retinoblastoma: fluoroscopic time and radiation dose parameters. A baseline study. (9th November 2016) - Boddu, Srikanth R; Abramson, David H; Marr, Brian P; Francis, Jasmine H; Gobin, Y Pierre
Abstract : Objective: To evaluate fluoroscopic time and radiation dose parameters, and factors affecting these parameters, during selective ophthalmic artery chemosurgery (SOAC) for retinoblastoma. Materials and methods: Retrospective review from the prospective database of all patients with retinoblastoma treated with SOAC over a 5-year period (September 2009–January 2015) at a single institution after receiving institutional review board approval. Patient demographics, arterial approach, access device, side of treatment, number of SOAC cycles/patient, number of drugs/SOAC, and radiation parameters (outcome variables), including the fluoroscopic time, dose–area product (DAP), and total radiation dose, were obtained from the database. Generalized linear regression was used for univariate and multivariate analysis of the outcome variables. Results: In 218 patients (M:F=94:124), 272 eyes were treated by 833 SOAC infusions during 792 procedures. Mean age, weight, SOAC cycle/patient, and drugs/cycle were 19±19.5 months, 11.4±6.4 kg, 2.72±1.6, and 2.48±0.8, respectively. Mean fluoroscopic time, DAP, and doses were 10.2±8.4 min, 218.7±240.8 cGy.cm 2, and 42.3±41.4 mGy, respectively. Radiation parameters (fluoroscopic time, DAP, and dose) were significantly lower (p<0.001) for the ophthalmic artery (OA) approach (7.5±5.4; 147.7±138.4; 28.5±29.4) than with middle meningeal artery (13.4±5.6; 242±138; 51.4±27) and balloon-assisted infusion in the internal carotid artery (ICA; 17.8±11.5; 449.8±361; 81.8±63.3). Radiation parameters for microcatheter access (8.6±7.1; 193.4±181.3; 42.3±37) were significantly lower (p<0.001) than with the ICA (17.8±11.5; 449.8±361; 81.8±63.3). Radiation parameters for bilateral IA chemotherapy (IAC; 16.8±11.6; 320.7±268.7; 60.8±45.6) were significantly higher (p<0.001) than for unilateral IAC (8.9±6.6; 212.7±247; 42±41). Conclusions: In SOAC for retinoblastoma, the OA approach, microcatheter access, and unilateral treatment were associated with significantly lower radiation parameters. We established benchmark radiation parameters for retinoblastoma SOAC in our patient cohort.